What snake is that? Common Australian snake species are frequently misidentified or unidentified - Wolfe, Ashleigh; Fleming, P.A.; Bateman, Bill (TAYLOR & FRANCIS LTD, 2020)
Human-wildlife conflicts are influenced by the public’s ability to identify dangerous species. We determined the snakes most commonly involved in conflicts by comparing types of “problem snakes” by location (urban/non-urban) for 9,627 calls to a Western Australian helpline. Of the 21% of cases identifying problem snakes, most urban sightings (82%) were for venomous brown snakes (Pseudonaja spp.) and tiger snakes (Notechis scutatus). We then tested the ability of Western Australians to discern dangerous species by displaying five common reptiles (brown snake/dugite, tiger snake, python, and two skinks) at four community events and asked attendees “what is it called,” “is it a snake,” and “is it venomous?” Respondents discerned snakes and lizards, but not species or venomous versus non-venomous. Adults correctly identified dugites more often than did children (82% and 48%, respectively). We recommend education (e.g., brochures, school programs) to help people identify and assess the danger of interacting with reptiles.